EFEKTIFITAS PENGGUNAAN MEDIA VIDEO PEMBELAJARAN PADA PELAJARAN AKHLAK TERHADAP MINAT BELAJAR DAN PRESTASI SANTRI KELAS II DAN III MADRASAH DINIYAH MIFTAHUN NAJAH JOSARI JETIS PONOROGO TAHUN PELAJARAN 2016/2017Ah - Achmad Kateno; Happy Susanto; Sigit Dwi Laksana (Universitas Muhammadiyah Ponorogo, 2017)
The background of the learning method that was held and the use of instructional media used in the madrasah diniyah miftahun najah and also analyzed the application of one of the medium of learning that is the use of video learning media Researchers took the research location in Madrasah Diniyah Miftahunnajah Josari Jetis ponorogo on the grounds that researchers have no similar research on Non-formal education institutions, using video media as one of the media in learning activities. Effectiveness of media usage of video on morals subject to the interest of learning and achievement of students of class II and III Madrasah diniyah miftahun najah, so that researchers can synchronize the relationship between the use of video media in learning morals towards student learning interest and learning achievement with the aim to evaluate teacher's learning in teaching using Media Video, to make it more interesting to understand the clarity of teachers as well as make the atmosphere of learning to be very fun. The results showed: (1) the use of learning video media has been in accordance with the rules and principles of good and right. (2) learners more interested in the use of video media in learning with percentage of 96% indicates that the use of highly effective learning video media used in learning activities (3) the correlation of the use of video learning media can increase student attendance so that interest in learning is also increased so that the achievement of the results Student learning also increases with a correlation of 0.51 the relationship of interest and learning achievement can be defined quite effectively to be applied in learning activities. (4) the use or utilization of such media is blocked by some madrasah facilities which can not be used because of such; Computer or laptop is damaged, LCD is broken, power outage and some are missing.